A Review Approach to Modeling, Analysis, and Design Framework for Wireless Sensor Network Health Monitoring Systems (Journal of Pharmaceutical Negative Results, 2022)
According to the results of the survey on Modeling, Analysis, and Design Framework for Wireless Sensor NetworkHealth Monitoring Systems, the current study is written. Wireless Sensor Networks (WSNs) are fast emerging as a keyenabling technology for a diverse variety of applications across a wide range of industries and disciplines. Recentbreakthroughs in wireless sensor networks (WSN) have made it feasible to deploy extensive health monitoring in boththe home care and hospital sectors, thanks to recent advances in wireless sensor networks. As a result of technologicaldevelopments in sensors, power-efficient integrated circuits, and wireless communication, it is now feasible to designphysiological sensor nodes that are compact and lightweight, low in cost, and capable of giving real-time information.Depending on their design, these nodes are capable of detecting, processing, and sending one or more vital signals,among other things. As a side benefit, they may be used to monitor one's health via wireless personal area networks(WPANs) or wireless body sensor networks, among other applications (WBSNs). Many studies have been undertakenand/or are currently being conducted in an effort to develop WBSNs that are flexible, reliable, secure, real-time, andpower-efficient, with the goal of using them in healthcare applications. WBSNs are a kind of wireless backhaul network(WBSN).